2014
DOI: 10.1504/ijwbc.2014.060355
|View full text |Cite
|
Sign up to set email alerts
|

Revising TAM for hedonic location-based social networks: the influence of TAM, perceived enjoyment, innovativeness and extraversion

Abstract: As a hedonic information system, a location-based social network (LBSN) is often seen as a promising innovative mobile service. However, research on LBSNs is still limited. Little is known about the factors influencing the intention to use LBSNs. Our study aims to explain the critical factors underlying the use of an LBSN, by developing a conceptual framework based on the technology acceptance model, the theory of diffusion of innovations and the five-factor model. To examine our proposed research model, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 51 publications
2
7
0
7
Order By: Relevance
“…Service convenience is started with a customer's fundamental desire to reduce their time and effort [7]. Studies agree with the opinion that if technology is perceived as easier to use, it is more likely to trigger system use behavior [4,12,39]. Han et al [14] showed that the perceived ease of use has a positive influence on behavioral intention toward kiosks at fast food restaurants.…”
Section: The Utaut2 Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Service convenience is started with a customer's fundamental desire to reduce their time and effort [7]. Studies agree with the opinion that if technology is perceived as easier to use, it is more likely to trigger system use behavior [4,12,39]. Han et al [14] showed that the perceived ease of use has a positive influence on behavioral intention toward kiosks at fast food restaurants.…”
Section: The Utaut2 Modelmentioning
confidence: 99%
“…On the other hand, since effort expectancy is a personal evaluation and social influences are social pressures, indeed, the effects of social influences have been proven to relate more to performance expectancy rather than to effort expectancy [11]. Researchers have also found that perceived pleasure is an important independent variable of perceived usefulness and ease of use [39,51,52]. In addition, consumers who are more familiar with a website based on previous visits are perceived to believe it is easier to use the site [53].…”
Section: Hypothesis 7 (H7) Habit Positively Relate To Behavioral Intentionsmentioning
confidence: 99%
“…Minat perilaku memiliki pengaruh positif terhadap penggunaan e-government learning di Taiwan (Shyu & Huang, 2011). Bouwman juga menyatakan dukungannya mengenai adanya pengaruh positif antara minat perilaku dan penggunaan jaringan sosial berbasis lokasi (Bouwman, 2011). Hasil penelitian Wu et al juga menyatakan bahwa minat perilaku berpengaruh positif terhadap penggunaan Web 2.0 (Wu et al, 2011).…”
Section: 1unclassified
“…Bouwman [13] was conducted to explain the factors that influence the intention to use and that underlie the actual use of the Location-Based Social Network (LBSN) information system. The results of this study indicate that perceived enjoyment has a positive effect on perceived usefulness, perceived ease of use and behavioral.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived ease of use is the degree to which people are confident that this system is easy to use. Bouwman [13] and Punnoose [14] used TAM by adding the perceived enjoyment variable, to get the results of acceptance of the e-learning information system. Information quality is an important point that must be fulfilled in supporting the benefits that must be achieved.…”
Section: Methodsmentioning
confidence: 99%